2016
DOI: 10.1007/s10207-016-0323-3
|View full text |Cite
|
Sign up to set email alerts
|

A key management scheme evaluation using Markov processes

Abstract: Content access control aims at ensuring that, in a system with several resources, users can only access resources they are authorized to. Resources are encrypted using cryptographic keys. Generating, distributing and renewing these keys are the challenges faced by key management schemes. While most of the existing key management schemes are typically evaluated by simulation. We propose, for the first time, to use Markovian processes for this purpose. Markovian processes give more accurate evaluation. The key t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The author of [1] has suggested that the main focus of Content Access Control is that the system and resources are access only by the authorized parties. The author of [2] has suggested that authentication using password is most prominent and user-friendly authentication process.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The author of [1] has suggested that the main focus of Content Access Control is that the system and resources are access only by the authorized parties. The author of [2] has suggested that authentication using password is most prominent and user-friendly authentication process.…”
Section: Review Of Literaturementioning
confidence: 99%